Involvement of the Na+/Ca2+ Exchanger in Ouabain-Induced Inotropy and Arrhythmogenesis in Guinea-Pig Myocardium as Revealed by SEA0400 - Hikaru Tanaka; Hideaki Shimada; Iyuki Namekata; Toru Kawanishi; Naoko Iida-Tanaka; Koki Shigenobu (Elsevier, 2007)
Involvement of the Na+/Ca2+ exchanger in ouabain-induced inotropy and arrhythmogenesis was examined with a specific inhibitor, SEA0400. In right ventricular papillary muscle isolated from guinea-pig ventricle, 1 µM SEA0400, which specifically inhibits the Na+/Ca2+ exchanger by 80%, reduced the ouabain (1 µM)-induced positive inotropy by 40%, but had no effect on the inotropy induced by 100 µM isobutyl methylxantine. SEA0400 significantly inhibited the contracture induced by low Na+ solution. In HEK293 cells expressing the Na+/Ca2+ exchanger, 1 µM ouabain induced an increase in intracellular Ca2+, which was inhibited by SEA0400. The arrhythmic contractions induced by 3 µM ouabain were significantly reduced by SEA0400. These results provide pharmacological evidence that the Na+/Ca2+ exchanger is involved in ouabain-induced inotropy and arrhythmogenesis. Keywords:: ouabain, Na+/Ca2+ exchanger, SEA0400, inotropy, arrhythmia